2021
DOI: 10.1007/s40122-021-00278-5
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Headache is Still Lurking in the Shadows

Abstract: Cluster headache, apart from its legendary reputation as the most violent headache that can exist, suffers from an average 60-month delay in diagnosis. The simplicity of the clinical manifestations, although dramatic, makes this delay inexplicable. The education of emergency department physicians and various specialists not specifically dedicated to headaches allows cluster headache to remain in a lurking position with flourishing periods of disease that are often unpredictable in both onset and disappearance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Therefore, the benefits of galcanezumab in preventing attacks in episodic CH patients did not outweigh its risks. In these countries, verapamil at high dosages is still used, but its use is limited by its cardiovascular risks, such as atrioventricular block [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the benefits of galcanezumab in preventing attacks in episodic CH patients did not outweigh its risks. In these countries, verapamil at high dosages is still used, but its use is limited by its cardiovascular risks, such as atrioventricular block [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster headache (CH) is one of the primary headache disorders. CH attacks are characterized by excruciating unilateral headache or facial pain accompanied by ipsilateral autonomic symptoms and restlessness or agitation [ 1 ]. CH patients suffer from a 60-month diagnostic delay despite the pain’s severity.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the correct diagnosis a crucial step towards effective treatment. Worldwide, the diagnosis of cluster headache is often delayed for years [ 115 , 116 ], and even more so in women [ 117 ] and adolescents [ 115 ]. This delay could be more pronounced in countries of the global south, where prevalent health issues like infectious diseases take precedence.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some reports of patients with comorbid migraine and cluster headache, where treatment of migraine with an anti-CGRP antibody improved both migraine and cluster headache [ 132 , 133 ]. In view of the high unmet need of cluster headache patients, associated with substantial suffering, and the limited evidence for existing preventive therapies, the EMA decision seems harsh, and creates substantial inequity [ 116 ].…”
Section: Introductionmentioning
confidence: 99%
“…This results in a limited understanding of the triggers and temporal course of the condition. 3,5 Variability in the clinical presentation, 6 misdiagnosis of symptoms as being migraine-related, 7 and the lack of understanding and awareness, 8 particularly among primary care physicians, contribute to diagnostic delays of several years for most patients with cluster headache. 7,9 A recent study identified that up to 50% of patients were diagnosed with cluster headache by a neurologist, indicating that misdiagnosis or inappropriate treatment may have come from other specialists or self-diagnosis.…”
Section: Introductionmentioning
confidence: 99%